Rwanda : A Case Study in Institutional Education Resilience - Arden, Richard; Claver, Yisa (World Bank, Washington, DC, 2014)
The Education Resilience Approaches (ERA) program seeks to provides a systematic evidence-based proves to improve the capacity of education system in fragile, conflict and/or violence affected situations (FCS). In this way, the ERA program complements the existing Education Department of the Human Development Network (HDNED) Systems Approach for Better Education Results (SABER) through the provision of context sensitive tools that support the development of academic and non-academic services leading to the protection of students well-being in context of adversity and the identification of education sector contributions to mitigate the social determinants of conflict and violence.